Appraisal Framework in Analyzing Learnersâ€™ Attitudinal Resources on Performing Of Mice and Men - Pasaribu, Truly Almendo (Indonesian Journal of EFL and Linguistics, 2020)
This paper is carried out to find out the attitudinal resources used by students in Play Performance class through appraisal framework (Martin & White, 2005). It focuses on how the students negotiate attitudes to express their feelings, judgements, and appreciation of â€œOf Mice and Menâ€ production process. The data for this qualitative study were collected from studentsâ€™ reflections which were selected purposely from different production and artistic divisions. It analyses 109 expressions based on three domains of attitudinal resources in the appraisal theory. The most frequently used resources are affect resources that serve to express studentsâ€™ positive or negative feelings. The findings show that although students experience a certain degree of insecurity [-security], they reveal positive inclination [+inclination] towards the production process. The judgement and appreciation resources are used to evaluate the behavior and learning processes. The discussion demonstrates that this systemic functional linguistic framework works as a solid basis to analyze studentsâ€™ reflections. This study implies that the appraisal framework can be one of the considerations in evaluating learnersâ€™ performance.